2021
DOI: 10.3389/fmicb.2021.639808
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence That Sunbirds’ Gut Microbiota Degrades Floral Nectar’s Toxic Alkaloids

Abstract: Orange-tufted sunbirds (Cinnyris osea) feed on the nectar of the tobacco tree (Nicotiana glauca) which contains toxic pyridine alkaloids characterized by high concentrations of anabasine and much lower concentrations of nicotine. We aimed at determining whether the gut microbiota of sunbirds harbors bacterial species that enable the birds to cope with these toxic alkaloids. An in vivo experiment that included 12 birds showed that inducing dysbiosis in sunbirds’ guts by the addition of sulfamethoxazole and trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Furthermore, P. xanthopygos can remediate the physiological consequences of BITC exposure and fully restore bird digestion and seedling growth. These results fit well with the previously suggested role of the gut microbiome in detoxification of “pollutants” in food 31 for insects 32 , rodents 33 and sunbirds 34 , but here we demonstrate that a specific bacterial species can mediate a multitrophic interaction positively affecting both bird digestive physiology and plant demographics (Fig. 6 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, P. xanthopygos can remediate the physiological consequences of BITC exposure and fully restore bird digestion and seedling growth. These results fit well with the previously suggested role of the gut microbiome in detoxification of “pollutants” in food 31 for insects 32 , rodents 33 and sunbirds 34 , but here we demonstrate that a specific bacterial species can mediate a multitrophic interaction positively affecting both bird digestive physiology and plant demographics (Fig. 6 ).…”
Section: Discussionsupporting
confidence: 93%
“…Six genera were more abundant in the intestines than in the cloaca: Balneimonas , Enterococcus ,Lactobacillus , Lactococcus , Psychrobacter , andRickettsiella (Figure 5a). Enterococcus has been found in the cloaca of birds (Jørgensen et al, 2017) andPsychrobacter has been found in the throats and guts of birds (Kämpfer et al, 2015), (Kämpfer et al, 2020).Lactobacillus and Lactococcus have been previously identified in the cloaca of birds (Allegretti et al, 2014;Gunasekaran, Trabelcy, Izhaki, & Halpern, 2021), but we found them at higher abundances in the intestines, which is similar to previous comparative studies (Hird et al, 2015;Capunitan et al, 2020). Enterococcus was more abundant in the intestines than the cloaca, gizzard, blood, and buccal cavity and more common in the blood than the gizzard (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of body sites also identified many additional taxa common to bird microbiomes and/or which are known pathogens:Campylobacter (Kapperud & Rosef, 1983;Hird et al, 2018),Cloacibacterium (Mandal et al, 2016).Comamonas (Kropáčková et al, 2017), Enhydrobacter (Kreisinger, Čížková, Kropáčková, & Albrecht, 2015), Methylotenera (Boukerb et al, 2021),Pseudomonas (Oprea, Crivineanu, Tudor, lOGOE, & Popa, 2010), Psychrobacter (Kämpfer et al, 2015), (Kämpfer et al, 2020).Sphingobacterium (Gunasekaran et al, 2021),Streptococcus (Devriese et al, 1994),Curtobacterium (Giorgio, De Bonis, Balestrieri, Rossi, & Guida, 2018), Kocuria (Braun, Wang, Zimmermann, Boutin, & Wink, 2018), Brevundimonas (Giorgio et al, 2018), Kingella (Foster et al, 2005), Micrococcus (Silvanose et al, 2001),Staphylococcus (Hermans et al, 2000),Lactococcus (Gunasekaran et al, 2021).Methylobacterium was found to be more abundant in the blood and buccal cavity more than the gizzard and more abundant in the buccal cavity than in the intestines and cloaca (Figure 6d, e, f, g). This is noteworthy as methylobacterium is known to be a contaminant in kits (Salter et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Vertebrates harbour diverse microbial communities within their gastrointestinal tract which influence numerous host‐associated functions, including dietary specialization (Gunasekaran et al, 2021; Kohl et al, 2016), immune system functioning (Broom & Kogut, 2018), metabolic capacity (Apajalahti & Vienola, 2016), and behaviour (Slevin et al, 2020). The complex symbiosis between a host and its microbiome is often a dynamic relationship, varying in response to both intrinsic and extrinsic factors (Adair & Douglas, 2017; Capunitan et al, 2020; Hird et al, 2015).…”
Section: Introductionmentioning
confidence: 99%